The behavioral intention of Malaysian students toward accounting discipline - Zandi Pour Joopari, GholamReza; Naysary, Babak; Say, Sok Kwan (Academy of Economic Studies Bucharest, Faculty of Accounting and Management Information Systems, 2013)
The aim of this study is to examine the factors affecting Malaysian male and female students’ intention to enroll in accounting programs. The study is based on the Theory of Reasoned Action as a theoretical framework. Based on Theory of Reasoned Action model, the factors that may affect students’ behavioral intention to choose accounting programs are categorized into three dimensions: attitudes toward choosing the program, subjective norm and amount of information on accounting. A questionnaire is employed to collect data from a sample of 400 male and female students in International Islamic University Malaysia and Tunku Abdul Rahman College in Malaysia currently enrolling in accounting programs. According to our results attitude and subjective norm have significant influence on behavioral intention of both male and female students to enroll in accounting programs. In case of amount of information on accounting, the results support its significant impact on males but not females’ behavioral intention to enroll in the program. Several implications and recommendations are also discussed in the light of our findings.